Tindakan Pengelolaan Pangan Rumah Tangga Dalam Memproduksi Limbah Pangan (Kasus: Desa Sukawening, Kecamatan Dramaga, Kabupaten Bogor) - Fhasia, Jihan Zannah; Antika, Sari Rezki; Friscariani , Fanny (Green Publisher Indonesia, 2025)
ood waste is a global problem faced by every country. Food and Agricultural Organization stated that Indonesia ranks second as the country that produces the most food waste in the world. The actions of the household food manager are based of various kinds of action motives. This study aims: (1)to identify the types and volumes of food waste produced by households through household food managers (2)to Identify forms of food action that can produce household food waste (3)to Identify food action motives that can produce food waste. household food waste (4)to Analyze the relationship between food actions and types and volume of household food waste (5to) Analyze the relationship between household characteristics and the actions of household food managers in producing food waste (6)to Analyze the relationship between action motives and actions to produce waste food. The research method chosen was a survey and observation of the main actors who manage household food (mother / wife) in one village in Bogor district. The sample respondents were 50 people selected by stratified random sampling technique. The relationship between variables was analyzed using the Rank Spearman correlation test. The results of this study indicates that: (1) there is a correlation between the action of food planning and the type of household food waste with a correlation value of 0.036 (<0.05), and (2) there is a correlation between the act of food consumption with the volume of food waste,with a significancy 0.025 (<0.05) (3) there is a relationship between action motives and social actions of food managers (4) there is a relationship between household layers and social actions of food managers, with a significance of 0.033 (<0.05) in the planning action, 0.003 (<0.05) for the storage action, and 0.034 (<0.05) for the consumption action and (5) there is no relationship between household size and the social action of food management, with the exception of consumption measures with a significance of 0.014 (<0.05)